Deepa Narayan (ed.). Measuring Empowerment: Cross-Disciplinary Perspectives. Washington, D.C.: The International Bank for Reconstruction and Development / The World Bank, 2005. Pages xx+475. Paperback. Price not given. (The Pakistan Development Review, 2004)
‘Empowerment’ has different meanings in different sociocultural and political contexts, and does not translate easily into all languages. Choosing indicators for measuring empowerment, therefore, depends on the social, economic, political, and cultural environment of the target population, and this multi-dimensional nature of empowerment complicates issues of measurement. This book brings forth the different indicators of empowerment in a cross-disciplinary perspective, underlining the challenge of evaluating empowerment and its contribution to development effectiveness and outcome.